2021
DOI: 10.14569/ijacsa.2021.0121107
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning based Forecasting Systems for Worldwide International Tourists Arrival

Abstract: The international tourist movement has overgrown in recent decades, and travelers are considered a significant source of income to the tourism economy. When tourists visit a place, they spend considerable money on their enjoyment, travel, and hotel accommodations. In this research, tourist data from 2010 to 2020 have been extracted and extended with depth analysis of different dimensions to identify valuable features. This research attempts to use machine learning regression techniques such as Support Vector R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…These models can potentially enhance the prediction accuracy of tourist arrivals by leveraging their ability to capture non-linear relationships and unveil hidden insights. Previous research has demonstrated the capacity of ML algorithms, such as artificial neural networks (ANNs) and support vector machines, to surpass conventional forecasting methods in prediction accuracy (Mishra et al, 2021). Moreover, the accessibility of rich social media data sources provides an opportunity to enhance predictions further by incorporating additional variables derived from online reviews and tourist discussions (Fronzetti Colladon et al, 2019;Li et al, 2020).…”
Section: Isuru Udayanganimentioning
confidence: 99%
See 1 more Smart Citation
“…These models can potentially enhance the prediction accuracy of tourist arrivals by leveraging their ability to capture non-linear relationships and unveil hidden insights. Previous research has demonstrated the capacity of ML algorithms, such as artificial neural networks (ANNs) and support vector machines, to surpass conventional forecasting methods in prediction accuracy (Mishra et al, 2021). Moreover, the accessibility of rich social media data sources provides an opportunity to enhance predictions further by incorporating additional variables derived from online reviews and tourist discussions (Fronzetti Colladon et al, 2019;Li et al, 2020).…”
Section: Isuru Udayanganimentioning
confidence: 99%
“…They suggest that forecasters in the tourism industry should only employ these two methods with serious consideration. Support vector machine (SVM) is applied for tourism demand analysis by (Mishra et al, 2021). SVM solves classification, non-linear regression estimation and prediction problems.…”
Section: Machine Learning Models For Tourism Demand Forecastingmentioning
confidence: 99%
“… Forster, Forster, Renfrew and Forster, 2020 , Knežević Cvelbar and Ogorevc, 2020 , Lenadora et al, 2020 , Martínez-López, Perez and Sánchez-Vizcaíno, 2009 , Mediouni, Madiouni and Kaczor-Urbanowiczc, 2020 , Mishra et al, 2021 , Palmer, 2016 , Sjödin et al, 2020 , Wiiava and Handoko, 2021 , Yang and Wong, 2020 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…Artificial intelligence and its machine learning methods have been applied in different areas and better results have been obtained than traditional methods such as the traditional regression with the normal equation [6]- [11]. In our work, a program has been developed to carry out regression using machine learning, as a case study the country of Peru was selected, which has been one of the countries with the highest mortality rate per inhabitant.…”
Section: Introductionmentioning
confidence: 99%